2017
DOI: 10.1002/lary.26821
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of bedside fiberoptic laryngoscopic recording on a tertiary consult service

Abstract: 4. Laryngoscope, 128:818-822, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…Prior studies have demonstrated strong inter‐rater agreement between resident and attending diagnoses on flexible laryngoscopy . However, in our study, the scope operator and the offsite reviewer did not always agree on the ability to visualize anatomical subsites, which is a more specific characteristic than diagnosis alone.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Prior studies have demonstrated strong inter‐rater agreement between resident and attending diagnoses on flexible laryngoscopy . However, in our study, the scope operator and the offsite reviewer did not always agree on the ability to visualize anatomical subsites, which is a more specific characteristic than diagnosis alone.…”
Section: Discussioncontrasting
confidence: 71%
“…A limited number of studies have investigated the value of recording endoscopic exams with smartphone adaptors in terms of diagnostic accuracy and resident education . However, only one previous study has looked at optical parameters .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical utility of smartphone adaptors for FNL was examined by Quimby et al in a systematic review, which identified high diagnostic accuracy, quality, and enhancement of resident education . Smartphone‐coupled FNL portable recording systems were compared to endoscopy towers by Lozada et al in a blinded study, and found good concordance between exams, having only to repeat 1 in 79 examinations (1.3%) due to image quality concerns . While this study did not use our adaptor specifically, we believe from experience that our adaptor provides similar image quality to commercial alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…There are a multitude of smartphone adaptors available from various third party manufacturers allowing for examinations to be recorded and viewed on a larger screen in real time. This offers diagnostic benefit, educational value, and reduces the need to re‐scope patients when findings are unclear to the primary operator . These adaptors are either designed for a specific brand of nasendoscopes, or can be generic telescope or binocular adaptors .…”
Section: Introductionmentioning
confidence: 99%